2007
DOI: 10.1007/s11684-007-0068-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperlipidemia on endothelial VCAM-1 expression and the protective role of fenofibrate

Abstract: The effect of hyperlipidemia and inflammation on endothelial functions was studied. The enrolled included control (basic chow), hyperlipidemia and fenofibrate-treated groups (high fat diet). The hyperlipidemia model was set up by four-week atherogenic diet, followed by a 16-week treatment in the fenofibrate-treated group (fenofibrate 40 mg/kg every day) and without treatment in the hyperlipidemia group, respectively. In the 20th week, serum lipid level and NO levels were measured, and the expression of vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Studies on animal models have shown that increased LDL levels promote the expression of VCAM1 in endothelial cells, and hypercholesterolemia can cause atherosclerosis-related pathophysiological changes in the arteries. 45,46 4J and 4K have clearly demonstrated prominent inhibition of aforementioned hyperlipidemic factors indicating their strong lipid lowering effects. Moreover, these compounds also reduced liver toxicity which is normally observed with the chronic use of statins.…”
Section: ■ Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies on animal models have shown that increased LDL levels promote the expression of VCAM1 in endothelial cells, and hypercholesterolemia can cause atherosclerosis-related pathophysiological changes in the arteries. 45,46 4J and 4K have clearly demonstrated prominent inhibition of aforementioned hyperlipidemic factors indicating their strong lipid lowering effects. Moreover, these compounds also reduced liver toxicity which is normally observed with the chronic use of statins.…”
Section: ■ Discussionmentioning
confidence: 98%
“…The species-specific antisense APOB inhibitors have been reported to reduce LDL, VLDL, and TC. , VCAM 1 is another well-recognized marker of atherosclerotic plaque vulnerability. Its overexpression has been observed over the complete course of plaque development. , VCAM 1 expression promotes the adhesion of leukocytes to the endothelial cells, accelerates the migration of adherent leukocytes along the endothelial surface, and facilitates the proliferation of smooth muscle cells. Therefore, VCAM 1 is considered a key player in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation